2017
DOI: 10.4103/1673-5374.200816
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen preconditioning improves postoperative cognitive dysfunction by reducing oxidant stress and inflammation

Abstract: Postoperative cognitive dysfunction is a crucial public health issue that has been increasingly studied in efforts to reduce symptoms or prevent its occurrence. However, effective advances remain lacking. Hyperbaric oxygen preconditioning has proved to protect vital organs, such as the heart, liver, and brain. Recently, it has been introduced and widely studied in the prevention of postoperative cognitive dysfunction, with promising results. However, the neuroprotective mechanisms underlying this phenomenon re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 107 publications
0
10
1
Order By: Relevance
“…Several studies have demonstrated that, since exposure to hyperoxia in clinical HBO therapy is rather brief, cellular antioxidant defenses are adequate and biochemical stress related to increased ROS is reversible [43,44]. More interestingly, it has been reported that the initial oxidative stress induced by HBO therapy acts as a trigger mechanism stimulating antioxidative and anti-inflammatory responses in cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that, since exposure to hyperoxia in clinical HBO therapy is rather brief, cellular antioxidant defenses are adequate and biochemical stress related to increased ROS is reversible [43,44]. More interestingly, it has been reported that the initial oxidative stress induced by HBO therapy acts as a trigger mechanism stimulating antioxidative and anti-inflammatory responses in cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of HBOT preconditioning in expected ischemia–reperfusion injury to the skin, spinal cord, brain, liver, kidney, and heart in various animal models. 913,1619 In addition, some clinical studies in humans reported that HBOT preconditioning in patients with coronary artery disease before coronary artery graft bypass demonstrated decreased myocardial injury, decreased duration of postoperative stay in the cardiac intensive care unit, decreased blood loss, fewer postoperative complications, and lesser financial burden. 14,19 The results of this study support the use of HBOT as an effective preconditioning treatment before abdominoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HBOT serves a vital role in enhancing BBB stability through MMP regulation [ 23 ], and can also decrease intracranial pressure and relieve cerebral edema [ 31 ]. Secondary effects of HBOT in the ischemic brain may be prevalent, due to the reduction of extracellular glutamate levels, causing neural dysfunction and excitotoxic death [ 44 ].…”
Section: Unpacking Mechanisms Of Action Of Hbot In Strokementioning
confidence: 99%
“…Alongside protecting BBB integrity and minimizing edema, HBOT may also protect energy metabolism and tissue perfusion by stabilizing glucose levels, preventing glutamate levels from increasing, lowering lactate/pyruvate ratios, and increasing Ang-2 activity. Protecting energy metabolism gave therapeutic effects, including increased microvessel density, reduced brain injury, and alleviated post-ischemic neurological deficits [ 44 , 134 ].…”
Section: Pre-clinical Findings With Hbot Preconditioning For Strokmentioning
confidence: 99%